Experimental and theoretical investigation of the characteristics of an electric response to an elastic impact excitation of piezo-containing heterogeneous materials; Russian Journal of Nondestructive Testing; Vol. 47, iss. 10 - Fursa T. V. Tatyana Viktorovna (2011, 2011)
Title screen